2006
DOI: 10.1007/s11240-005-9026-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of auxins, time exposure to auxin and genotypes on somatic embryogenesis from mature embryos of wheat

Abstract: The effects of different factors on the embryogenesis and plant regeneration from mature embryos of Russian spring and winter genotypes were studied. Embryogenic callus induction was achieved on MS medium supplemented with different concentrations of 2,4-D (2,4-dichlorophenoxyacetic acid), 2,4,5-T (2,4,5-trichlorophenoxyacetic acid) or Dicamba (3,6-dichloro-o-anisic acid). Although all auxins were able to induce callus from explants with high frequency (98-100%), Dicamba was more effective for the induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 27 publications
3
33
1
1
Order By: Relevance
“…After 30 days of culturing at 25 °C in the dark, the number of explants that produced embryogenic/nonembryogenic callus was scored. Endosperm-supported mature embryo culture was performed according to a protocol based on the combined application of 3,6-dichloro-o-anisic acid (Dicamba) and indoleacetic acid (IAA), for embryogenic callus induction (Filippov et al 2006, Miroshnichenko et al 2011. Prepared seeds were placed furrow down in Petri dishes and incubated at 25 °C in the dark for 25 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 30 days of culturing at 25 °C in the dark, the number of explants that produced embryogenic/nonembryogenic callus was scored. Endosperm-supported mature embryo culture was performed according to a protocol based on the combined application of 3,6-dichloro-o-anisic acid (Dicamba) and indoleacetic acid (IAA), for embryogenic callus induction (Filippov et al 2006, Miroshnichenko et al 2011. Prepared seeds were placed furrow down in Petri dishes and incubated at 25 °C in the dark for 25 days.…”
Section: Methodsmentioning
confidence: 99%
“…Mature wheat embryos are thought to be more recalcitrant to tissue culture than immature embryos, due to differences in the physiological and biochemical tissue status (Özgen et al 1998, Filippov et al 2006, Delporte et al 2014, Yang et al 2015. The acquisition of embryogenic competence in tissues of zygotic wheat embryos was shown to depend significantly on the endogenous level of growth regulators and total contents of phenols and soluble sugars (Jiménez andBangerth 2001, Yang et al 2015).…”
Section: о Alikina Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou and Lee (1984) were the first to achieve successful plant regeneration from wheat mature embryos. Subsequently, several workers have used various techniques for explant preparation, such as endosperm-supported embryo (Ozgen et al 1998;Filippov et al 2006), thin mature embryo fragments (Delporte et al 2001;Mendoza and Kaeppler 2002) and longitudinally bisected mature embryos (Yu et al 2008) and pretreatment of embryo with high levels of 2,4-D prior to culture or during culture for callus induction and plant regeneration. Since high levels of 2,4-D cause somaclonal variation in cereal crops, it has been argued to develop protocols with low levels of auxin (Mendoza and Kaeppler 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the effect of various factors, e. g., genotype (Ozgen et al 1996(Ozgen et al , 1998Zale et al 2004), type and concentration of auxin (Mendoza and Kaeppler 2002;Filippov et al 2006) and media components (Redway et al 1990;Mendoza and Kaeppler 2002;Greer et al 2009) either alone or in combinations has been evaluated for callus induction and subsequent regeneration. In spite of these studies, the regeneration has been found to be low (Ozgen et al 1998;Delporte et al 2001;Mendoza and Kaeppler 2002) and genotype dependent (Zale et al 2004;Filippov et al 2006;Yu et al 2008). One of the important factors which has not been paid proper attention is the role of non-embryogenic (NE) callus in regeneration from mature embryos (Redway et al 1990;Delporte et al 2001;Mendoza and Kaeppler 2002).…”
Section: Introductionmentioning
confidence: 99%